2017
DOI: 10.1016/j.childyouth.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Connectedness to family, school, peers, and community in socially vulnerable adolescents

Abstract: Youth who feel connected to people and institutions in their communities may be buffered from other risk factors in their lives. As a result, increasing connectedness has been recommended as a prevention strategy. In this study, we examined connectedness among 224 youth (ages 12–15), recruited from an urban medical emergency department, who were at elevated risk due to bullying perpetration or victimization, or low social connectedness. Regression analyses examined multiple domains of connectedness (family, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(174 citation statements)
references
References 67 publications
9
164
0
1
Order By: Relevance
“…The implication was that social guidance and counselling was seen to positively influence development of self-esteem that helps distance learners set personal study goals. This finding supports the finding of Foster et al (2017) that when learners feel less valued socially, they may not set personal study goals. Indicator (7) "Social guidance and counselling has helped me to develop positive attitude towards study" had a mean of 3.32 and a standard deviation of 1.32.…”
Section: Social Guidance Counselling and Self-esteemsupporting
confidence: 88%
“…The implication was that social guidance and counselling was seen to positively influence development of self-esteem that helps distance learners set personal study goals. This finding supports the finding of Foster et al (2017) that when learners feel less valued socially, they may not set personal study goals. Indicator (7) "Social guidance and counselling has helped me to develop positive attitude towards study" had a mean of 3.32 and a standard deviation of 1.32.…”
Section: Social Guidance Counselling and Self-esteemsupporting
confidence: 88%
“…In addition, PSMU can directly cause a decrease in social connectedness (McIntyre et al 2015;Pitmann and Reich 2016;Yao and Zhong 2014). Consequently, in a small study of adolescents (n = 224), Foster et al (2017) concluded that family connectedness protects adolescents against various psychological problems. Therefore, family life satisfaction appears to strengthen social connectedness and reduce PSMU.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that support from different relationship contexts has differential impacts on individual well‐being (Lee & Goldstein, ; Pössel et al, ), with the implications of specific sources of support varying depending on specific outcomes. During adolescence, perceptions of support from family and school are both particularly important in individual development and well‐being (e.g., Barrera & Li, ; Foster et al, ). Additional research shows that middle school youth classified as bullies or victims (or bully/victims) perceive lower levels of support as compared with their peers who are less involved in these behaviors (Malecki & Demaray, ), and that social support can function as a buffer regarding the deleterious link between peer victimization and symptoms of internalizing problems (Davidson & Demaray, ).…”
Section: Family and School Contexts And Peer Influencementioning
confidence: 99%
“…Recent research suggests that support from different relationship contexts has differential impacts on individual well-being (Lee & Goldstein, 2016;Pössel et al, 2018), with the implications of specific sources of support varying depending on specific outcomes. During adolescence, perceptions of support from family and school are both particularly important in individual development and well-being (e.g., Barrera & Li, 1996;Foster et al, 2017).…”
Section: Family and School Contexts And Peer Influencementioning
confidence: 99%